Caucasus Transport Corridor for Oil and Oil Products - World Bank (Washington, DC, 2013)
This study evaluates the potential demand for oil and oil products transport via the existing rail corridor in the Caucasus, taking into consideration the competition from alternative routes. It identifies potential bottlenecks that would prevent the potential traffic from using the corridor and proposes solutions for the physical and operational improvements to the corridor needed to attract the potential traffic. The report is based on a review of studies of oil production and transport, and interviews with oil producers, transportation intermediaries, railways, and ports in the region. The report begins with a discussion of the outlook for Caspian oil production and transport options for oil. Next, it discusses the physical and commercial constraints on the Caucasus rail corridor. It ends with a market analysis, strategies for attracting business, and significant actions needed to address the problems outlined previously in the report.